2014
DOI: 10.1371/journal.pone.0099236
|View full text |Cite
|
Sign up to set email alerts
|

Intraluminal Administration of Poly I:C Causes an Enteropathy That Is Exacerbated by Administration of Oral Dietary Antigen

Abstract: Systemic administration of polyinosinic:polycytidylic acid (poly I:C), mimics virally-induced activation of TLR3 signalling causing acute small intestine damage, but whether and how mucosal administration of poly I:C causes enteropathy is less clear. Our aim was to investigate the inflammatory pathways elicited after intraluminal administration of poly I:C and determine acute and delayed consequences of this locally induced immune activation. Intraluminal poly I:C induced rapid mucosal immune activation in C57… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 41 publications
1
18
0
5
Order By: Relevance
“…We also demonstrated here that orally administered L. plantarum MPL16 is able to differentially modulate the respiratory antiviral immune response. We reported previously that the improvement of IFN-β production by CD11c + SiglecF + alveolar macrophages and IFN-γ by CD3 + CD4 + T cells is related to the ability of immunobiotic treatments to enhance resistance to respiratory virus (39,40), in line with studies demonstrating that these immune cell populations are the main producer of IFNs during pulmonary viral infections (36,37). The increased levels of respiratory IFN-γ and IFN-β found in L. plantarum MPL16-treated mice correlated with the improved resistance of mice to RSV infection.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…We also demonstrated here that orally administered L. plantarum MPL16 is able to differentially modulate the respiratory antiviral immune response. We reported previously that the improvement of IFN-β production by CD11c + SiglecF + alveolar macrophages and IFN-γ by CD3 + CD4 + T cells is related to the ability of immunobiotic treatments to enhance resistance to respiratory virus (39,40), in line with studies demonstrating that these immune cell populations are the main producer of IFNs during pulmonary viral infections (36,37). The increased levels of respiratory IFN-γ and IFN-β found in L. plantarum MPL16-treated mice correlated with the improved resistance of mice to RSV infection.…”
Section: Discussionsupporting
confidence: 64%
“…In addition, it was reported that purified dsRNA from rotavirus is able to induce severe intestinal damage in mice through the activation of TLR3 signaling pathway (36). Moreover, it was also demonstrated that the intraperitoneal administration of the synthetic dsRNA poly(I:C) to mice mimics the inflammatory intestinal immune response elicited by rotavirus and induce mucosal erosion, villous atrophy, intestinal wall attenuation, and diarrhea (8,36,37). Interestingly, it was shown that the intestinal damage triggered by dsRNA-TRL3 interaction is mediated by the increased expression of IL-15 and retinoic acid early inducible 1 (RAE1) in IECs, which induce the activation of CD3 + NK1.1 + CD8αα + intraepithelial FIGURE 11 | Levels of bronchoalveolar lavage (BAL) interferons (IFN-β and IFN-γ), TNF-α, and interleukin 10 (IL-10) in mice orally treated with Lactobacillus rhamnosus CRL1505, Lactobacillus plantarum CRL1506, or L. plantarum MPL16 (10 8 cells/mouse per day for five consecutive days) and then challenged by the nasal route with RSV.…”
Section: Discussionmentioning
confidence: 99%
“…Intraluminal administration of peptides and poly I:C. p31-43 peptide (LGQQQPFPPQQPY, Biomatik), nonrelated peptide (NRP) (LD-PLIRGLLARPACALQV, Think Peptides), poly I:C (Sigma Aldrich), a combination of p31-43 peptide and poly I:C, or PBS were administered intraluminally during intestinal microsurgery as previously described (3). Briefly, mice were anaesthetized with 80 mg/kg ketamine and 10 mg/kg xylazine.…”
Section: Methodsmentioning
confidence: 99%
“…Poly(I:C), a synthetic analog of dsRNA, when administered intraperitoneally to mice mimics the local intestinal immune response elicited by an enteric viral infection (24, 25). Both purified RVs dsRNA and poly(I:C) are able to induce severe mucosal damage in the gut via TLR3 activation including villous atrophy, mucosal erosion, and gut wall attenuation (24).…”
Section: Intestinal Antiviral Innate Immune Response and Rotavirusmentioning
confidence: 99%